2018
DOI: 10.1111/resp.13247
|View full text |Cite
|
Sign up to set email alerts
|

Moving pulmonary rehabilitation forward in COPD: Stepping towards (home‐based) action

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/resp.13224/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In 2015, an ATS/ERS statement on pulmonary rehabilitation highlighted the urgent need to find novel programs as an alternative to the traditional outpatient service and stated that this was an essential approach to addressing the underutilization of the current model [11]. Over recent decades, deliberate efforts were devoted to evaluate the effects of alternative models in people with COPD [70]. Indeed, a number of robust randomized controlled trials have shown similar benefits with home-based pulmonary rehabilitation and tele-rehabilitation to the center-based model [71][72][73][74].…”
Section: Access To Telerehabilitation and Home-based Ratesmentioning
confidence: 99%
“…In 2015, an ATS/ERS statement on pulmonary rehabilitation highlighted the urgent need to find novel programs as an alternative to the traditional outpatient service and stated that this was an essential approach to addressing the underutilization of the current model [11]. Over recent decades, deliberate efforts were devoted to evaluate the effects of alternative models in people with COPD [70]. Indeed, a number of robust randomized controlled trials have shown similar benefits with home-based pulmonary rehabilitation and tele-rehabilitation to the center-based model [71][72][73][74].…”
Section: Access To Telerehabilitation and Home-based Ratesmentioning
confidence: 99%
“…A challenge currently affecting our ability to formulate evidence‐informed decisions regarding the suitability of PR for patients with asthma is the relatively small pool of research conducted using interventions befitting the modern‐day definition of PR . Precisely what constitutes sufficient education and behaviour change is subject to some debate; however, many studies in the field are more accurately defined as exercise training . One interesting issue arising from the Cochrane review by Carson et al is uncertainty regarding the applicability of the evidence to ‘typical’ patients encountered in adult clinical respiratory medicine.…”
Section: Pr In Asthmamentioning
confidence: 99%
“…They evaluated 10 trials: outpatient and home‐based exercise programmes appeared equally effective at improving quality of life and exercise capacity, based on low to moderate quality evidence . An accompanying editorial stressed that further work should be done to overcome barriers to attendance at pulmonary rehabilitation programmes . This will involve developing novel models of home‐based care …”
Section: Copdmentioning
confidence: 99%
“…An accompanying editorial stressed that further work should be done to overcome barriers to attendance at pulmonary rehabilitation programmes . This will involve developing novel models of home‐based care …”
Section: Copdmentioning
confidence: 99%